El indio miserable: nacimiento de la teoría legal en la América colonial del siglo XVI. - Cunill, Caroline (CIICLA, Universidad de Costa Rica, 2012)
The concept of miserable applied to the indios is fundamental in order to understand early colonial Spanish American legislation and institutions. Both the discovery of new occurrences of the term miserable and the publication by Carlos Sempat Assadourian of a petition presented by fray Bartolomé de Las Casas before the Audiencia de los Confines (1545), in which the Dominican friar first developed this concept, justify its reconsideration. In order to provide new insights, a multidisciplinary approach is envisaged, given that our object is to highlight the links between law, politics and society in this analysis of the origin, the diffusion, the semantic content and the political usage of the term miserable applied to the Indians.